(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2017)
Although labour is considered as a normal physiological process, it can produce significant pain, requiring appropriate pain management. A painful labour also had detrimental effects on the mother and fetus. Ideal labour analgesia technique should dramatically reduce the pain of labour, while allowing the parturient to actively participate in birthing experience and have minimal adverse effects on the fetus and progress of labour. Epidural analgesia and opioids are often used for management of labour pain. Epidural analgesia is an effective method for managing labour pain. Studies have indicated that the procedure has few contraindications and few side-effects. The study was done to see the efficacy and safety of epidural analgesia with conventional analgesia (Inj. Pethidine and phenergan) during labour. In this study, pregnant women with active labour (Cervical dilation 4cm) were grouped into two A & B. Group A received epidural analgesia (0.125% Bupivacaine & 50 microgram Fentanyl) & group B received conventional analgesia (Inj. Pethidine & phenergan). Then the subjects were followed up and outcomes were recorded in a preformed data collection sheet. All data were analyzed by computer based software SPSS version 15. The study demonstrated a significantly earlier onset of effective analgesia in epidural group than that in the conventional group. The pain score at onset of analgesia and at different time intervals following induction and at the time of delivery were appreciably lower in women receiving epidural analgesia than those receiving conventional analgesia (p<0.001). There was no significant difference between epidural and conventional groups in terms of complications like nausea and/or vomiting (p=0.431), prolonged 2nd stage of labour (p=0.127), mode of delivery (Normal / Instrumental / Cesarean) (p=0.455). Neonatal outcome was evaluated in terms of APGAR score at 1& 5 minutes of birth in both groups which showed no significant differences (p=0.401and p=0.536 respectively). So, epidural analgesia is an effective analgesia during labour. JCMCTA 2016 ; 27 (2) : 12 - 17